Polymer blend nanocomposites for polymer electrolyte membrane fuel cell (PEMFC) applications - Siti Maznah, Kabeb; Nurul Huda, Abu Bakar (Elsevier Ltd, 2023)
This chapter introduces polymer blend nanocomposites for polymer electrolyte membrane fuel cell (PEMFC) applications, beginning with a brief introduction to the fuel cell (FC) principle. Overviews of the working principles, the equations of the governing reactions, fundamental electrochemistry, and the leading applications are presented. Moreover, the proton exchange membrane fuel cell or PEMFC, membrane electrode assembly, membrane polymer blend for FC, and organic-inorganic composite membranes are detailed. A comprehensive description is provided of the types of polymer used in polymer blends, and the recent advances in additive-enhanced polymer electrolytes are also discussed.